Diversity of plants as a food supplement and medicine for livestock in cattleman communities of Wonosobo, Central Java, Indonesia - FIKA NUR APRILIA; FRANSISCA AMELIA KARTIKA ARDHYANTI; HANA PARAMESTI; GHAZY AQILA SHANDY PRABOWO; RAISA NOOR SAFIRA; NISYAWATI NISYAWATI; AHMAD DWI SETYAWAN (Smujo International, 2025)
Abstract. Aprilia FN, Ardhyanti FAK, Paramesti H, Prabowo GAS, Safira RN, Nisyawati, Setyawan AD. 2025. Diversity of plants as a food supplement and medicine for livestock in cattleman communities of Wonosobo, Central Java, Indonesia. Nusantara Bioscience 17: 84-95. The Wonosobo community in Central Java, Indonesia mostly participates in agriculture and animal husbandry. Individuals engaged in agriculture and animal husbandry exhibit a significant reliance on local resources for the management of food production and animals. This study aimed to find plant diversity that serves as animal feed and supplements for cattle in Wonosobo. The investigation was conducted in October 2024 in the Kalibawang Sub-district of Wonosobo, Central Java, Indonesia, utilizing data gathered from four villages: Dempel, Kalialang, Karangsambung, and Mergolangu. This study included direct surveys and comprehensive interviews with 126 livestock farmers to collect data. The study documented 74 plant species from 37 families utilized as animal feed. The predominant plant families were Fabaceae, Euphorbiaceae, Asteraceae, Poaceae, and Moraceae, encompassing several plants with considerable potential for application in feed, medicine, and animal supplements, presenting a promising perspective for the future of agriculture in Wonosobo. Of the 78 species, 15 were utilized by the inhabitants of Kalibawang Sub-district for medicinal applications, including wora-wari (Hibiscus rosa-sinensis), sengon laut (Paraserianthes falcataria), brotowali (Tinospora cordifolia), coconut (Cocos nucifera), papaya (Carica papaya), jackfruit (Artocarpus heterophyllus), Gliricidia (Gliricidia sepium), sulanjana (Pennisetum purpureum), cassava (Manihot esculenta), jenu (Derris elliptica), banana (Musa x paradisiaca), ginger (Zingiber officinale), turmeric (Curcuma longa), candlenut (Aleurites moluccanus), and mahogany (Swietenia mahagoni). The highest UV index was recorded in Artocarpus heterophyllus Lam and Carica papaya L., with a value of 0.023. The highest indices for RFC (0.37) is Calliandra calothyrsus Meissn and IAR (Informant Agreement Ratio) (0.94) is Artocarpus heterophyllus Lam; however, the highest ICF (Informant Consensus Factor) index was associated with the diarrhea (0.66).